Analisis Pemanfaatan ChatGPT sebagai Inovasi Pembelajaran dan Dampaknya Terhadap Orisinalitas Karya Akademik Mahasiswa UIN Malang - Putri, Aulia Zahro Fiba; Fikri, Afidatul (LoroNG: Media Pengkajian Sosial Budaya, 2025)
This research analyzes the utilization of ChatGPT as a learning innovation and its impact on the originality of student academic work at UIN Malang. Using a descriptive qualitative approach, data was collected through semi-structured interviews with 16 students from the Faculty of Tarbiyah and Teacher Training (FITK), selected purposively. Findings indicate that ChatGPT functions as a digital scaffold based on Vygotsky's theory, enhancing task efficiency, understanding of complex material, and learning motivation. However, critical threats emerge, such as the temptation for plagiarism, dependency that reduces creativity, and content inaccuracy within the context of Islamic scholarship. The majority of students are aware of the risks of disguised plagiarism and develop independent strategies. Within the Ulul Albab value framework, the research formulates a mitigation model based on spiritual-ethical integration “Cybernetic Ulul Albab": Hybrid Digital Scaffolding (lecturer-student-AI collaboration), a Spiritual-Intellectual Validation System (checking for alignment with Islamic values), and a Critical Co-Creation Framework (transforming AI output into original work). The conclusion affirms that the successful implementation of ChatGPT in PTKIN (State Islamic Religious Higher Education Institutions) depends on balancing professional maturity and spiritual depth, positioning it as a complement to, rather than a replacement for, the human intellectual process.